Development of Alternative Scenario for Ethiopia2019;s Electricity Sector by LEAP Software (Global Journals of Research in Engineering, 2013)
Ethiopia a country in Africa is endowed with renewable energy sources such as hydro solar and wind These energy sources are economically exploitable and if electrical energy could be prouduced it could be surplus beyond the country s demand Exporting electrical energy Ethiopia could earn more money without disturbing environment as it is a global warming issue now-a-days But due to lack of technology the rich renewable resources are not utilized properly and as a result only 15 of the population of the country have access to electricity In this paper based on moderate scenario an alternative scenario for Ethiopia s electricity sector will be developed to meet its energy demand upto the year 2030 For alternative scenario the time range from year 2008 to 2030 was considered in LEAP software In the alternative scenario hydro and geothermal were judiciously selected as the source of energy Solar energy was not selected due to its upfront cost which is unbearable by any developing countries Wind energy was not selected because of seasonal variations in energy production around the year
Keywords: ethiopia energy scenario; hydro energy; geothermal energy; energy demand; environmental issue; energy export